2016
DOI: 10.1109/tcomm.2016.2584601
|View full text |Cite
|
Sign up to set email alerts
|

On the Superiority of Improper Gaussian Signaling in Wireless Interference MIMO Scenarios

Abstract: Abstract-Recent results have elucidated the benefits of using improper Gaussian signaling (IGS) as compared to conventional proper Gaussian signaling (PGS) in terms of achievable rate for interference-limited conditions. This paper exploits majorization theory tools to formally quantify the gains of IGS along with widely linear transceivers for MIMO systems in interferencelimited scenarios. The MIMO point-to-point channel with interference (P2P-I) is analyzed, assuming that received interference can be either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23]. More recently, in [24], the authors showed the advantages of improper signaling in a multiuser scenario where a point-to-point link coexists with a multiple access channel.…”
Section: Introductionsupporting
confidence: 57%
“…Similar DoF results were derived for the four-user interference channel in [14]. After that, a number of new works has emerged, and the payoffs of improper signaling have been revealed for different multiuser scenarios such as the interference channel [3][4][5]15], Z-interference channel [6,[16][17][18], broadcast channels with linear precoding [19,20], underlay and overlay cognitive radio networks [7,8,21] and relay channels [22,23]. More recently, in [24], the authors showed the advantages of improper signaling in a multiuser scenario where a point-to-point link coexists with a multiple access channel.…”
Section: Introductionsupporting
confidence: 57%
“…Finally, it should be pointed out that the channel model we consider here (the standard pointto-point Gaussian MIMO channel under interference constraints at the transmitter) is different from the Gaussian interference channel (G-IC) where multi-user interference is present at each receiver and there is no interference constraint at the transmitters, as in e.g. [21]- [29]. In the latter case, the capacity and optimal signaling are not known in general, even for the 2-user SISO channel [21] (it is not even known whether Gaussian signaling is optimal in general), except for some special cases, such as strong and weak interference regimes [22] [23], so that various bounds [24][25] and ad-hoc signaling techniques [26]- [29] are used instead.…”
mentioning
confidence: 99%
“…[21]- [29]. In the latter case, the capacity and optimal signaling are not known in general, even for the 2-user SISO channel [21] (it is not even known whether Gaussian signaling is optimal in general), except for some special cases, such as strong and weak interference regimes [22] [23], so that various bounds [24][25] and ad-hoc signaling techniques [26]- [29] are used instead. On the contrary, optimal signaling is known to be Guassian for the channel model considered here and the capacity can be expressed as an optimization problem over all feasible transmit covariance matrices.…”
mentioning
confidence: 99%
“…In the second type, we derive the whole rate region for a specific channel realization. It is worth mentioning that both types of numerical examples are common for rate region analysis (please refer to [6], [9], [11]).…”
Section: Numerical Resultsmentioning
confidence: 99%